TESTING THE VALIDITY OF CAPITAL ASSET PRICING AND THE FAMA AND FRENCH MODELS IN THE STOCK EXCHANGES OF G7 COUNTRIES - Ma, Lianjie (2021)
This research aimed to see if the CAPM, FF3FM, and FF3FM could explain the abnormal portfolio return variances. The explanatory factors were the market risk factor, RM-Rf, size risk factor (SMB), BE/ME risk factor (HML), RMW, and the CMA. The FF5FM was created to put the model's results to the test. The study's findings are based on each stock index's monthly excess return. ACCORDING TO THE ESTIMATION RESULTS, the CAPM and FF3FM and the FF5FM offer limited explanations on the varying portfolio returns of portfolios of main stock indexes in G7 countries throughout the world. The study results reveal statistically significant differences in the excess stock index returns realized in the stock markets. The Dow and Jones industrial average has the highest monthly returns of 0.53%, followed by the Nikkei, while the CAC 40 has -11.16% average monthly returns. CAPM is valid in these stock indices, including DAX, Dow and Jones, MIB, Nikkei, and the TSX index returns, while the FF3FM can validly explain the stock index returns to DAX and MIB. The results show that instead of the explanatory powers increasing after introducing the two additional models to move from CAPM to FF3FM, the weakness of the explanatory power. According to the findings of the three-asset pricing, CAPM, FF3FM, and FF5FM, no model can be judged more effectively to explain all nations' market index returns fully. As a result, portfolio managers must conduct more in-depth research about the needs and models to determine which model is best for the specific market under consideration.